Development and In-Vitro Evaluation of Vinpocetine Loaded Bi-Layer Tablet Using Different Polymers - Mithilesh Kumar Jha, Md. Zakaria Faruki, Md. Habibur Rahman, Md. Mofizur Rahman, Md. Mesbah Uddin Talukder (Journal of Applied Pharmaceutical Science)
The present study has investigated various ways to formulate a bi-layer tablet dosage form containing an immediate release and a sustained release portion of a neuroprotective compound named vinpocetine. The bi-layer matrix tablet was prepared by simple compression of the SR granules and IR granules of vinpocetine. The sustained release effect of vinpocetine was achieved with polymers methocel K15M CR, kollidon SR and carbomer 934P. Physical properties of powders, granules and the finished tablets were evaluated. The drug release study of the tablets was studied for 2 hours in 0.1N HCl followed by 8 hours in pH 6.8 phosphate buffer as media using United States Pharmacopoea (USP) XXII paddle type dissolution apparatus. The effect of above mentioned polymers on vinpocetine release profile was investigated. The MDT values of all the formulations were calculated and correlated with the rate retardation capacity of drug release of the polymers used. The release rate of vinpocetine immediate release layer was found to be influenced little by kollidon CL and direct compressible grade lactose. The release rate, extent and mechanisms of sustained release layers were found to be governed by the nature and the extent of the polymer used in the formulation. Kinetic modeling of dissolution profiles reveled that vinpocetine release mechanism ranges from the anomalous / non – fickian transport to super case II transport in the given situations. These studies indicated that the proper balance between a matrix forming agent and a channeling agent can produce a drug dissolution profile similar to a theoretical dissolution profile will overcome the disadvantages of conventional tablets of vinpocetine.
Keywords: Vinpocetine, Bi-Layer Tablet, Sustained Release, Mean Dissolution Time (MDT), Anomalous / non – Fickian transport, Super case-II.